Investigation of role of vascular endothelial growth factor, Annexin A5 and Apelin by immunohistochemistry method in placenta of preeclampsia patients - Colcimen, Nese; Bulut, Gülay; Ergul Erkec, Ozlem; Ragbetli, Murat Cetin (Cellular and Molecular Biology, 2017)
Preeclampsia is a disease characterized by hypertension and proteinuria occurred after 20 weeks of gestation. Preeclampsia is a major cause of maternal and fetal morbidity and mortality. The pathophysiological mechanism of preeclampsia is not known exactly yet. Preeclampsia endothelial cell dysfunction, associated with inadequate trophoblastic invasion is characterized by abnormal placentation. Vascular endothelial growth factor (VEGF) according to is an angiogenic cytokine, Annexin A5 is among endogenous peptides are both expressed from placental trophoblasts and Apelin is a multifunctional peptide and expressed by placental trophoblasts and endothelial cells. It was aimed to investigate roles of these parameters occurring in preeclampsia and to compare immunoreactivity of them in normal and preeclamptic placenta. In this study, placentas were collected from 20 normotensive pregnant women as controls, 16 mild-preeclamptic pregnant women, and 16 severe preeclamptic women. VEGF, Annexin A5 and Apelin were examined in samples of placenta tissues by streptavidin-biotin-peroxidase complex immunohistochemical methods. Immunoreactivity scores (IRS) were obtained for each parameter. VEGF and Apelin IRS were increased significantly in preeclamptic groups compared with control group (p <0.026, p<0.002 respectively). But Annexin A5 IRS was decreased significantly in preeclamptic groups compared with control group (p<0.04). In correlation with the intensity of disease, increase in VEGF and Apelin, and decrease in Annexin A5 supports roles of hemo-dynamic alterations in fetoplacental circulation and structural alterations in uteroplacental bed occurring in preeclampsia.